Human Development and Social Inclusion in an Urbanizing World: Introduction to the special issue - Mitchell, Ann (Ensayos de Política Económica, 2019)
This introduction to the special issue on the theme of Human Development and Capabilities begins by explaining key concepts of the capability approach and presenting examples of how the approach has been applied to the analysis of urban development issues. It then summarizes the four articles and two book reviews that comprise the issue. Common themes highlighted in this issue include the territorial dimension of poverty and inequality in Latin America, the challenges to assessing multidimensional poverty and social exclusion in the face of data limitations and the importance of participatory methods in research.